2016
DOI: 10.1002/clen.201501007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Purification of Membrane‐Bound Azoreductase From Azo Dye Degrading Shewanella sp. Strain IFN4

Abstract: Azo dyes can be degraded by azoreductases that achieve initial decolorization of the dye molecule through cleavage of the azo bond. Here we characterized membrane-bound azoreductase enzyme expressed by Shewanella sp. strain IFN4, which is a particularly efficient azo dye degrading bacterium. Initial studies showed that this bacterium was capable of decolorizing a wide variety of azo dyes including Reactive Black 5, Acid Red 88, Direct Red 81, Acid Yellow 19, and Disperse Orange 3. These structurally different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In the current study, maximum decolorization was obtained over a wide range of temperatures (Figure C). Similar observations were obtained by Rumky and Imran et al However, Du et al reported that Aeromonas sp. showed a good decolorization potential at a relatively high temperature (40 °C).…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, maximum decolorization was obtained over a wide range of temperatures (Figure C). Similar observations were obtained by Rumky and Imran et al However, Du et al reported that Aeromonas sp. showed a good decolorization potential at a relatively high temperature (40 °C).…”
Section: Discussionsupporting
confidence: 87%
“…The known genetic mechanism for azo dye degradation is the catalysis of azo dyes into aromatic amines by the bacterial enzyme azoreductase (Imran et al 2016b). This protein is very important and carries out the reduction cleavage of azo bond (-N=N-).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of aerobic and anaerobic bacteria such as Pseudomonas sp., Bacilus subtilis, Geobacillus sp., Escherichia coli, Rhabdobacter sp., Enterococcus sp., Staphylococcus sp., Corneybaterium sp., Lactobacillus sp., Xenophilus sp., Clostridium sp., Acinetobacter sp., Micrococcus sp., Dermacoccus sp., Rhizobium sp., Proteus sp., Morganella sp., Aeromonas sp., Alcaligenes sp., Klebsiellla sp., Shewanella sp., and Alishewanella sp. have been extensively reported for resulting good biodegradation of azo dyes [2,[19][20][21]. Pseudomonas sp.…”
Section: Enzyme-mediated Degradation Of Azo Dyes Bacterial Strain Capmentioning
confidence: 99%
“…The primary step in bacterial decolorization is either aerobic or anaerobic or by sequential method [22], followed by reductive cleavage of the azo bond. Under anaerobic condition, azo dyes are degraded to colorless amine that is carcinogenic in nature [23] and are further degraded by aerobic processes [19]. Sequential microaerophilic or aerobic processes can be used where aromatic amine produced in microaerophilic condition is further degraded in aerobic condition [15,23,24].…”
Section: Enzyme-meditated Decolorization and Degradation Of Azo Dyementioning
confidence: 99%